2009
DOI: 10.1073/pnas.0902161106
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome transfer produces a predictable cellular phenotype

Abstract: Cellular phenotype is the conglomerate of multiple cellular processes involving gene and protein expression that result in the elaboration of a cell's particular morphology and function. It has been thought that differentiated postmitotic cells have their genomes hard wired, with little ability for phenotypic plasticity. Here we show that transfer of the transcriptome from differentiated rat astrocytes into a nondividing differentiated rat neuron resulted in the conversion of the neuron into a functional astro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 28 publications
(26 reference statements)
0
63
0
1
Order By: Relevance
“…We have previously shown that the transfer of transcriptome (TIPeR) from a rat astrocyte into a rat neuron converts the electrically active neuron into an electrically quiescent tAstrocyte cell (10). We asked whether the change in expression profile (i.e., modulation of relative abundance of gene products) could transdifferentiate electrically quiescent cells into electrically excitable cells.…”
mentioning
confidence: 99%
“…We have previously shown that the transfer of transcriptome (TIPeR) from a rat astrocyte into a rat neuron converts the electrically active neuron into an electrically quiescent tAstrocyte cell (10). We asked whether the change in expression profile (i.e., modulation of relative abundance of gene products) could transdifferentiate electrically quiescent cells into electrically excitable cells.…”
mentioning
confidence: 99%
“…During irradiation, a tiny, submicrometre-sized pore, lasting fractions of a second, is generated on the plasma membrane. Cell viabilities greater than or equal to 90 per cent are often reported in the literature (Tirlapur & Konig 2002;Kohli et al 2005a;Peng et al 2007;Baumgart et al 2008;Lei et al 2008;Uchugonova et al 2008b Baumgart et al 2008;Uchugonova et al 2008b), and mRNA (Barrett et al 2006;Sul et al 2009). Recently, our own laboratory has even shown that a single 100 nm gold particle can be optically tweezed and subsequently injected into a cell (McDougall et al 2009; as discussed in more detail later).…”
Section: Optical Transfection With Fs-pulsed Sources: Targeted Singlementioning
confidence: 99%
“…The field is at an exciting juncture with the publication of two seminal papers from the Eberwine group (Barrett et al 2006;Sul et al 2009). Here, the focus of study was not the technique of optical injection itself, but the application of the technique to biological questions difficult to answer using other methods.…”
Section: Single Cell Analysismentioning
confidence: 99%
“…The amplified aRNA can also be used to confirm cell phenotype conversion studies in which a full set of mRNAs from one cell type are transfected into a different cell type in order to induce transition of the phenotype of the latter cell type into that of the former, a procedure developed by the lab and known as TIPeR. 17 These studies are particularly useful for studying disease states and cell phenotypes and such studies are currently ongoing in the lab. RT-PCR or qPCR can be performed on the amplified material to confirm the expression of cell-specific genes.…”
Section: Applicationsmentioning
confidence: 99%